2014
DOI: 10.1038/tpj.2014.59
|View full text |Cite
|
Sign up to set email alerts
|

Association of OPRM1 A118G variant with risk of morphine-induced respiratory depression following spine fusion in adolescents

Abstract: The μ1 opioid receptor (OPRM1) genetic variant A118G results in decreased μ-receptor binding potential in the brain and increases morphine requirement. We hypothesized that OPRM1 A118G polymorphism will affect morphine-induced respiratory depression (MIRD) risk in children receiving morphine. A prospective genotype-blinded study was conducted in 88 healthy adolescents (11–18 years; 67% female, 85% Caucasian) who underwent spine fusion for scoliosis. They were followed for 48 h postoperatively for MIRD, pain sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 51 publications
3
27
1
Order By: Relevance
“…Twin studies have revealed significant heritability (30%) for RD from opioids [62]; contributing nongenetic risk factors like female sex and medical comorbidities have been described [63][64][65]. Our study strengthens the evidence for FAAH associations with morphine outcomes in children, adds to the genetic risk factors reported previously -OPRM1 [66] and ABCB1 [67] and expands the knowledge base toward identifying genetic risk signatures for RD in children [68]. FAAH inhibitors have been explored for treatment of pain and nausea [69,70]; our findings spur further investigation of these agents to alter risk of opioid RD.…”
Section: Discussionsupporting
confidence: 76%
“…Twin studies have revealed significant heritability (30%) for RD from opioids [62]; contributing nongenetic risk factors like female sex and medical comorbidities have been described [63][64][65]. Our study strengthens the evidence for FAAH associations with morphine outcomes in children, adds to the genetic risk factors reported previously -OPRM1 [66] and ABCB1 [67] and expands the knowledge base toward identifying genetic risk signatures for RD in children [68]. FAAH inhibitors have been explored for treatment of pain and nausea [69,70]; our findings spur further investigation of these agents to alter risk of opioid RD.…”
Section: Discussionsupporting
confidence: 76%
“…However, the use of morphine is at risk of addiction and respiratory depression (Chidambaran et al 2015). Many physicians and patients are reluctant to use morphine for fear of respiratory depression and the lack of comprehensive understanding about morphine.…”
Section: Discussionmentioning
confidence: 99%
“…This mutation leads to decreased cell surface expression and overall receptor stability combined with more subtle effects on the binding affinity of opioid peptides and small molecules (69,70). Increasing evidence suggests that this variant may alter pain threshold levels, sensitivity to clinically used opioids, and risk of opioidinduced respiratory depression (71)(72)(73). At a structural level, the direct consequence of this variant remains unknown owing to truncations in the presumably flexible amino terminus required for crystallography.…”
Section: Genetic Variation In Opioid Receptor Structurementioning
confidence: 99%